Mexico : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2012)
Mexico is an open economy with strong real and financial links to the rest of the world with risks of spillovers from global turbulence. Recent gains in market share in the U.S. manufacturing market are owed to improved relative unit labor costs and reemergence of a location advantage. Mexico's current fiscal framework requires measures to offset the emerging challenges of a decline in oil revenues and the projected increase in health- and pensions-related spending. The sustained increase of bank credit after the global crisis has been reversed. The effects of migration depend on labor reform.